Seafood stewardship in crisis - Jacquet, Jennifer; Pauly, Daniel; Ainley, David; Holt, Sidney; Dayton, Paul; Jackson, Jeremy (Nature (London), 2010)
Accreditation Services International, a company in Bonn, Germany, oversees the assessors, who use an open-to-the-public system involving independent scientists, input from stakeholders and external peer review. In our view, the certification system creates a potential financial conflict of interest, because certifiers that leniently interpret existing criteria might expect to receive more work and profit from ongoing annual audits. The MSC states: "It is not the purpose of the Objections Procedure to review the subject fishery against the MSC Principles and Criteria for Sustainable Fisheries, but to determine whether the certification body made an error."